Assessment of the impact of body mass index on right ventricular systolic and diastolic function in patients with type 2 diabetes mellitus using two-dimensional speckle tracking imaging - Wenwen Wang; Yuanyuan Peng; Kun Zhao; Ziwei Zheng; Jiangbo Feng; Chengfang Zou; Yongchun Sun; Bo Lin; Liping Wang; Bing Hu; Shaoling Yang (Frontiers in Clinical Diabetes and Healthcare, 2026)
Objective To evaluate the impact of different body mass index (BMI) levels on right ventricular (RV) systolic and diastolic function in patients with type 2 diabetes mellitus (T2DM) using two-dimensional speckle tracking imaging (2D-STI), and to provide imaging reference for the early screening of subclinical RV dysfunction in overweight and obese patients with T2DM. Method A total of 67 newly diagnosed T2DM patients (disease duration ≤6 months, treatment-naïve) and 61 age-matched healthy controls who presented to our hospital from January 2022 to June 2023 were enrolled. All participants with hypertension, cardiovascular diseases, or bronchopulmonary diseases were excluded. According to T2DM status and BMI levels, the subjects were divided into four groups: non-T2DM normal weight group (BMI 18.5-23.9 kg/m 2 , n=30), non-T2DM overweight/obese group (BMI ≥24.0 kg/m 2 , n=31), T2DM normal weight group (n=33), and T2DM overweight/obese group (n=34). The primary endpoint was RV free wall global longitudinal strain (RVFWS), and the secondary endpoint was the early-to-late diastolic strain rate ratio (SRe/SRa). The sample size was calculated based on a pilot study (expected effect size =1.8, α=0.05, statistical power = 80%), with a minimum required sample size of 28 per group, which was met by the actual enrollment. 2D-STI was performed to measure longitudinal strain at the basal, mid, and apical segments of the RV free wall, and the average value was defined as RVFWS. Early diastolic strain rate (SRe) and late diastolic strain rate (SRa) were recorded, and the SRe/SRa ratio was calculated. Two-way analysis of variance (ANOVA) was used to compare differences among groups, and multiple linear regression analysis was performed to identify independent predictors of RV functional parameters and to test for interaction effects. Continuous variables were expressed as mean ± standard deviation, and post-hoc multiple comparisons were conducted using the least significant difference (LSD) method. We integrated interpretations of main and interaction effects to minimize Type I error inflation. Results Statistically significant differences in RVFWS and SRe/SRa ratio were observed among the four groups (all P < 0.05). Two-way ANOVA revealed significant interactions between BMI and T2DM for both RVFWS and SRe/SRa ratio (all P < 0.001). Compared with Group A, RVFWS and SRe/SRa decreased stepwise in Group B, Group C and Group D, with the greatest decline observed in Group D. Multiple linear regression demonstrated that BMI was significantly negatively associated with RVFWS and the SRe/SRa ratio in the overall cohort (P < 0.001). Full 95% confidence intervals were calculated and reported for all correlation and regression outcomes.